Physicochemical Properties of Banana Peel Starch from Musa Paradisiaca fa. Corniculata at Different Maturity Stages - Mohamad Fauzi, Ani Fadhilah; Zainal Abidin, Munira; Zulhilmi Cheng, Mohamad Zulhafiz Shafiq (Enhanced Knowledge in Sciences and Technology, 2025)
This study explores the physicochemical properties of banana peel starch from Musa Paradisiaca Fa. Corniculata (Horn Banana or Pisang Tanduk) is across different maturity stages, focusing on its potential applications in the food and industrial sectors. The analysis encompasses parameters such as pH, moisture content, viscosity, gelatinization temperature, melting point, iodine calorimetry, and angle of repose. Starch was extracted from banana peels at unripe, ripe, and overripe stages using wet extraction methods. Results revealed significant variations in physicochemical properties based on maturity stages. Unripe starch exhibited the highest gelatinization temperature and stability, making it suitable for high-temperature applications. In contrast, ripe starch showed optimal viscosity, indicating its potential as a thickening agent. Overripe starch demonstrated lower amylose content and higher pH, suggesting reduced structural integrity but improved compatibility in acidic formulations. These findings highlight the unique characteristics of banana peel starch and its adaptability across diverse applications. This research not only promotes the valorization of banana peel waste but also contributes to sustainable resource utilization in developing bio-based products.